β-ADRENOSENSITIZING ACTIVITY OF BLOOD SERUM IN PATIENTS AFTER AN ACUTE CORONARY EVENT AND ITS RELATIONSHIP TO PHYSICAL EXERCISE - S. V. Malchikova; E. N. Sizova; V. I. Tsirkin; S. F. Gulyayeva; A. N. Trukhin; V. A. Vedernikov (Российский кардиологический журнал, 2003)
β-Adrenosensitizing activity of blood serum diluted by 50-, 100-, 500-, 1000- и 10000, from 10 almost healthy elderly people and 40 patients with acute coronary event (ACE), was studied on longitudinal strips of uterine horns of 31 rats. 10 of them underwent physical exercising during rehabilitation, thus increasing working capacity and left ventricle contractility. Serum from normal subjects showed no β-adrenosensitizing activity, i.e. contained no endogenous blockers of β-receptors. In patients with ACE including those performing physical exercise, all serum dilutions, particularly 500- and 1000-fold, increased the inhibiting effect of epinephrine (10-8 g/ml) which is explained by the presence of endogenous β-receptor sensitizers (EBRS) - like, probably, histidine, tryptophan and tyrosine. In ACE β-adrenosensitizing activity and, therefore, the EBRS level, is below the values in normal subjects, increasing in physical exercise. An opportunity of increasing the effectiveness of β-activity upon heart and vessels during rehabilitation following an ACE, and by using aromatic aminoacids and drugs (Preductal or Mildronate) is discussed.